The influence of brand image and ticket prices on repurchase intention of Citilink airlines with satisfaction as an intervening on flight routes Jakarta - Kulonprogo - Hananto, Pandu Tri; Bernarto, Innocentius (Enrichment : Journal of Management, 2025)
Competition in the aviation market in Indonesia is a type of Oligopoly competition market, because it is only operated by a few airlines, especially domestic flights. One of the airlines that has contributed to the development of economic activity in Indonesia is PT Citilink Indonesia. This study aims to test influence of Brand Image and price variables on Repurchase intention through Satisfaction among Citilink passengers in Indonesia. So that the research results are more accurate, this research will focus on the Jakarta-Kulonprogo flight. Quantitative data analysis is data analysis in the form of numbers through statistical calculations based on questionnaire answers from respondents. The results of these scores or values are then subjected to statistical analysis carried out with the help of the Smart-PLS program to prove the relationship between the research variables